2016
DOI: 10.1002/cctc.201501292
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Deoxygenation of Fructose to Furfuryl Alcohol by Sequential Dehydration and Decarbonylation

Abstract: Fructose was deoxygenated to furfuryl alcohol (FFA) by tandem dehydration and decarbonylation in one pot over the AlCl3⋅6 H2O/Pd(OAc)2 catalyst combination to give a high FFA yield of 40.6 %. AlCl3⋅6 H2O behaves as an effective Lewis acid to catalyze the dehydration of fructose to 5‐hydroxymethylfurfural (HMF), and subsequently, Pd(OAc)2 catalyzes the removal of a CO moiety from HMF to produce FFA selectively. The hydroxyl group on the HMF intermediate was stabilized by poly(1‐vinyl‐2‐pyrrolidinone) through an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Furfural and HMF decarbonylation is primarily performed in 1,4‐dioxane (Scheme ), a polar aprotic solvent often used for lignocellulose pretreatment. However, the short‐term acute toxicity of 1,4‐dioxane (symptoms include vertigo, drowsiness, anorexia, and ear/nose/lung irritation), and long‐term effects resulting from chronic exposure (such as hepatotoxicity, neurotoxicity, and carcinogenicity in animal models) suggest dioxane is not suitable for the sustainable, large‐scale processing of biomass.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furfural and HMF decarbonylation is primarily performed in 1,4‐dioxane (Scheme ), a polar aprotic solvent often used for lignocellulose pretreatment. However, the short‐term acute toxicity of 1,4‐dioxane (symptoms include vertigo, drowsiness, anorexia, and ear/nose/lung irritation), and long‐term effects resulting from chronic exposure (such as hepatotoxicity, neurotoxicity, and carcinogenicity in animal models) suggest dioxane is not suitable for the sustainable, large‐scale processing of biomass.…”
Section: Resultsmentioning
confidence: 99%
“…Although some operate under relatively mild conditions, most require high catalyst loading (from 0.5 mol % for Ir to 16 mol % for heptanal decarbonylation over Pd) . In a recent example, Hu and co‐workers reported the tandem dehydration–decarbonylation of fructose using a Lewis acid for dehydration (aluminum chloride) and palladium acetate for decarbonylation, but required 11 mol % Pd to achieve full conversion with a turnover frequency (TOF) of only approximately 3 h −1 . Heterogeneous catalysts reported for HMF and furfural decarbonylation are all Pd‐derived (Scheme ), but a significant improvement in efficiency (TOF range from 1–26 h −1 ) and robustness is needed.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing of concern about environmental problems and cost‐efficiency, the concept of “one‐pot” reaction, using multifunctional catalyst or catalyst combination, have been developed to directly convert monosaccharide (fructose, glucose and xylose) to furan derivatives in batch or fixed‐bed reactor . In particular, J. H. Dai and co‐worker developed a batch process combined dehydration and decarbonylation, in which the fructose could be directly converted to FOL (yield 40.6 %). Additionally, it was shown by Cui .…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the zeolites and Pd‐based catalysts, conversion of fructose into FOL is achieved in continuously fixed‐bed reactor, eliminating the need for separation step (see Scheme and Supporting Information S1). Unsatisfactorily, in most reported examples dealing with the production of FOL from HMF or carbohydrates, the toxic dioxane, which is hazardous to environment and operators, was used as solvent ,,,…”
Section: Introductionmentioning
confidence: 99%
“…In most of the reported protocols, 5-HMF has been majorly highlighted for the decarbonylation of À CHO functional group under the influence of various metals such as Pd, Rh, Ru and Ir-catalysed conditions. [5][6][7][8][9][10][11][12][13] In 2015, Rauchfuss and co-workers reported the Pd/C-catalysed decarbonylation of 5-HMF to corresponding furfuryl alcohol synthesis in good yield at 120°C in 1,4-dioxane solvent conditions (Scheme 1a). [14] Furthermore, Kawanami et al also observed the labile nature of the aldehyde (À CHO) group of 5-HMF under Pd/Al 2 O 3 catalyst conditions under compressed CO 2 and got furfuryl alcohol as major product at 145°C (Scheme 1b).…”
mentioning
confidence: 99%